2021
DOI: 10.3390/cancers13133176
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Upregulation of MAGE-A Isoforms Promotes Breast Cancer Cell Aggressiveness

Abstract: After decades-long efforts to diagnose and treat breast cancer, the management strategy that has proved most successful to date is molecular-subtype-specific inhibition of the hormone receptors and HER2 that are expressed by individual cancers. Melanoma-associated antigen (MAGE) proteins comprise >40 highly conserved members that contain the MAGE homology domain. They are often overexpressed in multiple cancers and contribute to cancer progression and metastasis. However, it remains unclear whether the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…investigated the MAGEA12 in breast cancer and found that it promotes malignancy. [ 30 ] MAGEA12 expression is contributed to histone modifier proteins. This protein up-regulation attributes to epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…investigated the MAGEA12 in breast cancer and found that it promotes malignancy. [ 30 ] MAGEA12 expression is contributed to histone modifier proteins. This protein up-regulation attributes to epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…This protein up-regulation attributes to epigenetic modifications. [ 30 ] The functional enrichment analysis of differentially-expressed CTA genes showed that MAGEA3, 6, 12, and CSAG3 are involved in binding proteins. Maxfield et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAGEA12 has been shown to act as a prognostic-related gene in gastric cancer [20]. In addition, overexpression of MAGEA12 is involved in the pathogenesis of human cutaneous squamous cell carcinoma and can also promote invasion of breast cancer cells [21,22]. The study by Chuzhao Lin et al reported that cancer/testis antigen CSAGE was concurrently expressed with MAGE in chondrosarcoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer germline antigens derive from proteins that are naturally expressed during foetal development and in certain types of tumours but are usually unexpressed in adult normal tissues. The most investigated cancer germline antigens are NY-ESO-1 and MAGE-A antigens, first reported in patients with synovial cell sarcoma or melanoma [ 36 , 37 , 38 , 39 , 40 , 41 ], but also described in several other types of tumours [ 38 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Differentiation antigens are specific proteins from tissue or cells, both healthy and affected, where the tumour is occurring, but that are not expressed in other tissues, as CD19 in most of B cell lymphomas [ 35 , 54 ] or gp100 and MART-1 in melanoma [ 55 , 56 ]).…”
Section: T Cell Response To Different Type Of Tumoural Antigensmentioning
confidence: 99%